Diet and physical activity influence the composition of gut microbiota, benefit on Alzheimer’s disease - Jinyue Zhou; Min Tang; Wanyi Li; Rui Fang; Chunlan Tang; Qinwen Wang (Food Science and Human Wellness)
Alzheimer’s disease is a neurodegenerative disease with complex etiology. Gut microbiota influences the gut-brain axis, which may affect pathways related to the pathogenesis of Alzheimer’s disease. Additionally, diet and physical activity are likely to affect the pathology of Alzheimer’s disease as well as the gut microbiota. This demonstrates that it may be possible to prevent or halt the progression of Alzheimer’s disease by regulating the gut microbiota using diet and physical activity strategies. Therefore, the present study reviews the association between these two interventions and gut microbiota in the human body. It also summarizes how these two interventions benefit Alzheimer’s disease. Furthermore, the primary limitations of these two interventions are discussed and promising strategies are proposed, which may be beneficial to further study and develop the intervening measure for the progression of Alzheimer’s disease.